DELIK PIDANA KORUPSI & PELAPOR KORUPSI DILINDUNGI UNDANG-UNDANG - harmono . (Fakultas Hukum Universitas Swadaya Gunung Jati, 2015)
AbstractThe act of corruption is a highly negative and inhumane act as it puts serious damage on the implementation order of state and nation. This type of crime is always carried out jointly by a certain group of people who hold the power and this is used a strategy to block the exposure of the case to the law authorities from their inside. This is in contrary with the idea that the prevention and eradication of corruption are the right and responsibility of all components of the nation. In addition, Indonesian government has made some regulations as a means to prevent and prosecute the acts of corruption, and protect any party that participate in reporting the acts of corruption.Keywords: Acts of Corruption, Law Prevention and Protection